Fundamentals of deductive program synthesis - Manna, Z.; Waldinger, R. (IEEE transactions on software engineering, 1992)
An informal tutorial for program synthesis is presented, with an emphasis on deductive methods. According to this approach, to construct a program meeting a given specification, the authors prove the existence of an object meeting the specified conditions. The proof is restricted to be sufficiently constructive, in the sense that, in establishing the existence of the desired output, the proof is forced to indicate a computational method for finding it. That method becomes the basis for a program that can be extracted from the proof. The exposition is based on the deductive-tableau system, a theorem-proving framework particularly suitable for program synthesis. The system includes a nonclausal resolution rule, facilities for reasoning about equality, and a well-founded induction rule.< >